Periodontal status in chronic periodontitis depressed patients on desvenlafaxine: An observational study - Anu Bhatia; Rajinder Kumar Sharma; Shikha Tewari; Satish Chander Narula; Hitesh Khurana (Wolters Kluwer Medknow Publications, 2018)
Background: A wide variety of drugs have the potential to affect immune and inflammatory responses of periodontium. A class of antidepressant drug, selective serotonin and norepinephrine reuptake inhibitors, has shown anti-inflammatory function. The aim of the present study is to explore the effect of desvenlafaxine on clinical periodontal parameters in patients with chronic periodontitis. Materials and Methods: The patients were divided into two groups as follows: test group (n = 63) comprised of participants on 50 mg once-daily dose of desvenlafaxine for ≥2 months and control group (n = 72) included participants who were yet to be prescribed medication for depression. Periodontal parameters of both the groups were analyzed and compared statistically. Results: Participants taking desvenlafaxine revealed lower values of periodontal parameters as compared to those in control group. The number of pockets with greater depth and clinical attachment loss was greater in control group. Conclusion: In our study, patients on desvenlafaxine were associated with less pocket depth and bleeding on probing.